Determinants of Female Fertility Based on Social and Cultural Perspective in South Sulawesi Province - Marwadi, Muh Chalik (Populasi, 2023)
The phenomenon of the population continuing to grow rapidly means that the government needs to focus its efforts on controlling fertility. This is because fertility is more complex than mortality, in which a woman can only die once but can give birth many times. This research aims to find out the determinants of fertility from a social and cultural perspective. This research used data from 3,108 women aged 15 to 49 years old from the 2017 Indonesia Demographic and Health Survey (IDHS). Apart from that, in-depth interviews were also conducted with female respondents aged 15 to 49 years old as the main research subjects. On the quantitative data, binary logistic regression analysis was carried out to test the determinants of fertility and the results showed that education, work status, media exposure to family planning, use of contraceptives, and area of residence had affected fertility. Apart from that, there are also cultural phenomena, such as panaik money, which influence women’s fertility.